Perovskite Solar Cells: Revealing Underlying Processes Involved in Light Soaking Effects and Hysteresis Phenomena in Perovskite Solar Cells (Adv. Energy Mater. 14/2015). Issue 14 (July 2015) - Zhao, Chen; Chen, Bingbing; Qiao, Xianfeng; Luan, Lin; Lu, Kai; Hu, Bin
<x xml:space="preserve">Abstract</x> Light‐soaking and hysteresis phenomena can reveal the bulk and interfacial polarization effects on photovoltaic processes in perovskite solar cells. In article number 1500279, Bin Hu and co‐workers report the use of frequency‐dependent impedance and time‐dependent photoluminescence measurements to determine that bulk and interfacial polarizations are internally coupled in developing short‐circuit current, open‐circuit voltage, and fill factor through charge dissociation, transport, and collection in light‐soaking and hysteresis phenomena.